Adobe® Photoshop® Elements® 3.0 Idea Kit - Matthews, Lisa (Adobe Press, 2004)
You may already know how to use Photoshop Elements to edit your digital images or to create some basic special effects. But if you want to take those skills further--using your finely crafted images to produce a variety of professional-looking projects--you need this guide! In these pages, design pro Lisa M. Matthews shows you how to take advantage of all of Photoshop Elements' features--including those new to 3.0, like Photomail and an improved Review Mode--to create everything from postcards and flyers to personal Web pages, Web galleries, custom CD and DVD covers, and more. After learning the basics of image correction (including how to color images by hand and add borders), you'll find basic layout strategies for a slew of projects. As your knowledge grows, so does the complexity of the projects, so that by the end of the volume, you'll be creating slide presentations, Web pages and banners, and more. Best of all, the companion CD includes working templates of the book's projects and a trial version of the software.